Natural and Naturally Derived Photoinitiating Systems for Light-Based 3D Printing - Vazquez-Martel, Clara; Mainik, Philipp; Blasco, Eva (Organic Materials, 2022)
Photoinitiating systems (PISs) are key components in photocurable formulations (inks) for three-dimensional (3D) printing. Natural PISs are promising and more environmentally friendly alternatives to conventional photoinitiators. These systems offer enhanced features such as less toxicity and therefore, higher biocompatibility. Furthermore, they can be found in a large “color palette” variety (absorbing in the different regions of the UV-visible spectrum) enabling new possibilities in the field of 3D printing. In this review, we outline the current efforts to implement natural and naturally derived PISs in light-based 3D printing. First, recently applied natural PISs and their performance for light-based 3D printing are discussed. In a second part, an overview of naturally derived PISs including the most common synthetic strategies are provided. Last, current challenges as well as future perspectives of the field are discussed.IntroductionNatural Photoinitiating SystemsNaturally Derived Photoinitiating SystemsConclusions and Outlook
Keywords: natural products; photoinitiating systems; photopolymerization; 3D printing